Globalising Migration History : the Eurasian Experience (16th-21st Centuries). - Lucassen, Jan (Studies in global migration history., 2014)
Globalizing Migration History presents a new universal method to quantify and qualify cross-cultural migrations, which makes it possible to detect regional trends and explain differences in migration patterns across the globe in the last half millennium.